#TITLE_ALTERNATIVE# - Gustiandi (NIM 132 00 119), Budhi
Abstract: Active noise control is a noise attenuation system that is achieved by using controlled acoustic source in order to attenuate the undesired noise. Active noise control concept is destructive interferetion between the undesired noise and the other acoustic source (antinoise) which have phase that opposite one another. Active noise control system eficiently attenuate low frequency noise where passive methods is unefective or too cost and bulky. This final project research report will discuss active noise control system design for attenuate the noise that have broadband frequency response characteristic. Active noise control system is used based on digital signal processing development board ADSP-21262 EZ-KIT Lite. The algorithm that is used is a derivative adaptive algorithm from Least Mean Square (LMS) algorithm called Filtered-X Least Mean Square (FxLMS) algorithm. Implementation design is done for noise attenuation experiment in a duct. The experiment consist of three process, simulation, hardware frequency responce characteristic testing, and software algorithm design testing.